Approaches of Gender Sociology towards Violence of Women, in Metropolitan Lima - Blossiers Mazzini, Carolina (2019)
In Metropolitan Lima the interactions that take place between women and men are produced and reproduced within the family, where social and cultural representations of the feminine and masculine are constructed. Also in the family, sexuality, violent behavior, norms and values are configured. We also notice how from the emergence of private property, monogamous marriage, the patriarchal family and relations of power; generates the inequality of the male in relation to the woman who is considered superior, and the opportunities of women are extinguished to develop fully in the social life. The World Health Organization & the Pan American Health Organization (1998) show that the problem of violence against women starts from: childhood, continues in adolescence, reproductive stage to old age. In addition, the World Health Organization (2016) points out that Peru ranks third in the world for sexual violence and femicide, after Ethiopia and Bangladesh.